Ketidaktransparanan Penegakan Hukum Dan Implikasinya Terhadap Prinsip Keadilan Sosial di Indonesia - Kinari, Qoshi Fadilah Marsya; Sholehah, Catherina Dewi; Antoni, Herli (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
The lack of transparency in law enforcement in Indonesia has caused various problems, including injustice and reduced public trust in the legal system. This study aims to explore the impact of legal non-transparency on the principle of social justice based on Pancasila, especially the fifth principle. Using a literature review method, this study identifies that unfair and discriminatory legal practices, such as in the case of e-KTP project corruption, exacerbate social inequality and strengthen negative perceptions of legal integrity. Transparent law enforcement is seen as an important solution to address this problem. This study recommends legal system reform by increasing transparency, accountability, and public access to the judicial process to achieve equitable justice in accordance with the values of Pancasila.